Functional Independence and Disability Evaluation in Stroke Patients: Optimal Cutoff Scores for a Pictorial-Based Longshi Scale, Barthel Index, and Modified Rankin Scale - Liu, Xiangxiang; Zhou, Mingchao; Zhao, Jingpu; Gao, Yan; Wang, Yao; Zhou, Jing; Wan, Li; Nie, Guohui; Wang, Yulong (Frontiers in Neurology, 2022)
Introduction: The modified Rankin Scale(mRS) and Barthel Index(BI) are widely used to measure functional outcomes worldwide. Longshi Scale(LS) was designed to improve the simplicity and convenience of measuring functional outcomes in the Chinese context. This study aimed to identify the optimal cutoff scores of LS and BI according to the mRS in Chinese stroke patients with different levels of functional disability. Methods: The mRS, BI, and LS were applied to evaluate functional independence and disability in 7364 stroke patients. Stroke patients were categorized into bedridden, domestic, and community groups in advance using the LS, indicating severe, moderate, and mild functional disability, respectively. The optimal cut-off scores of the LS and BI according to the mRS were identified via sensitivity, specificity, and Youden’s index and stratified by different levels of functional disability determined by LS. We also plotted the receiver operator characteristic(ROC) curves of sensitivity and specificity and determined the area under the curve(AUC). Results: In the bedridden group, LS and BI cutoff scores with the highest Youden’s index were 5 and 10 for mRS 4, and the AUCs for the ROC curve were 0.848 and 0.863 for mRS 4. In the domestic group, LS and BI cutoff scores with the highest Youden’s index were 5 and 65 for mRS 3, and the AUCs for the ROC curve were 0.796 and 0.826 for mRS 3. In the community group, LS cutoff scores with the highest sum of sensitivity and specificity were 9, 9, and 8 for mRS 0, 1, and 2, respectively, while the BI cutoff scores with the highest sum of sensitivity and specificity were 100, 100, and 95, respectively, while the AUCs for the ROC curve were 0.697 and 0.735 for mRS 2, 0.694 and 0.716 for mRS 1, and 0.628, and 0.660 for mRS 0. Conclusions: The mRS is more precise to determine mild functional disability, whereas BI can provide more specific information on moderate and severe levels in stroke patients. Although LS was less precise to determine moderate and severe levels than BI, it is much simpler and more convenient to be applied to a large-scale population.